The role of C4d and donor specific antibodies in face and hand transplantation—a systematic review - Huelsboemer, Lioba; Moscarelli, Jake; Dony, Alna; Boroumand, Sam; Kochen, Alejandro; Knoedler, Leonard; Yu, Catherine T.; Hauc, Sacha C.; Stögner, Viola A.; Formica, Richard N.; Lian, Christiane G.; Murphy, Georg F.; et al. (Frontiers in Transplantation, 2024)
To date, little is known about the mechanisms of rejection in vascularized composite allotransplantation, particularly for antibody mediated rejection. Additionally, no clear guidelines exist for the diagnosis and management of antibody-mediated rejection in vascularized composite allotransplantation. A systematic review of electronic databases (Embase and PubMed) was conducted to evaluate the relationship of donor specific antibodies and C4d deposition in correlation with cellular rejection following hand and face transplantation reported by centers between 1998 and July 2023. We extracted data on serum donor specific antibodies at the time of biopsy proven rejection according to Banff classification and C4d staining of target tissues. Mann-Whitney U tests were performed to compare rejection grade between groups divided by status of C4d deposition and serum donor specific antibodies, and Fisher's Exact test was used to assess association between the two markers. This review adhered to PRISMA guidelines. A total of 26 patients (5 face, 21 hand) were identified and data on 90 acute rejection episodes with information on Banff grade, donor specific antibody status, and C4d deposition were available. Donor specific antibodies were found to be associated with higher rejection grade (p = 0.005). C4d was not found to be associated with higher rejection grade (p = 0.33). Finally, no significant association was found between concurrent status of the two markers (p = 0.23). These findings suggest that the presence of donor specifc antibodies may be associated with higher grades of acute cellular rejection following hand and face transplantation. More consistent reporting on rejection episodes is needed in order to better understand antibody-mediated rejection in vascularized composite allotransplantation.